Clinico-Bacteriological Evaluation of Surface and Core Tonsillar Tissue in Chronic Tonsillitis - Shrestha, Kumar; Paudel, Dhundi Raj; Mahaseth, Subhash Chandra; Pokhrel, Sandeep (Journal of Nepalgunj Medical College, 2023)
Introduction: Chronic tonsillitis is the most common disease for Otolaryngologists. Effective treatment of tonsillitis depends on knowledge of the infecting organisms. Controversy regarding the treatment of tonsillitis based on throat culture report still persists. There is always a dilemma whether the antibiotics prescribed for tonsillitis are sufficient for the different organisms on the surface and core of the tonsils. If surface culture is a determinant of bacteriology of the core, then rational therapy could be aimed at organisms cultured by surface swabs. Aims: To study the correlation of bacteria isolated from the surface and core of the tonsil in chronic tonsillitis and antibiotic sensitivity of the bacterial isolates. Methods: This was a prospective study carried out on fifty patients, who underwent tonsillectomy for chronic tonsillitis. The swabs obtained from the surface of the tonsil before tonsillectomy and the core of the tonsil post tonsillectomy were sent for isolation of micro-organisms. Antibiotic sensitivity test was performed by Kirby-Bauer Disk Diffusion method on the bacterial isolates. Results: Bacterial growth was detected in 74% of the total sample, in cultures from the surface or the core tissue or both. 78% of surface samples versus 70% of tonsillar core samples revealed bacterial growth. No pathogens were isolated in 26% of samples. Staphylococcus Aureus and Group A β hemolytic streptococcus were the most commonly isolated organisms. Antibiotics sensitive against these pathogens include Amoxycillin-Clavulanic acid, Cefpodoxime, Amikacin, Levofloxacin, Doxycycline, and Nitrofurantoin. Conclusion: Our study shows that surface culture does not reliably predict core pathogens in cases of chronic infection. Staphylococcus Aureus and Group A β hemolytic streptococcus were the most commonly isolated organisms from the surface and core of the tonsil. So the antibiotics effective against these organisms should be chosen.